THE IMPORTANCE OF FOREIGN LANGUAGE LEARNING - Teshaboyeva Nafisa Zubaydulla qizi,; Aktamova Farangiz Farrux qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract In  the  modern  globalized  world,  foreign  language  learning  has  become  an essential component of education, communication, and professional development. The ability  to  speak  more  than  one  language  enhances  cognitive  abilities,  academic achievement, cultural awareness, and career opportunities. This article examines the importance of foreign language learning from cognitive, educational, social, cultural, and professional perspectives. Based on scientific research and international studies, the  paper  highlights  how  language  learning  strengthens  mental  skills,  promotes intercultural understanding, and supports global cooperation. Furthermore, the study emphasizes  the  role of  foreign language  education in preparing  individuals  for  the demands  of  the  global  labor  market  and  digital  communication  era.  The  findings suggest that foreign language learning is not only an academic skill but also a lifelong investment in personal growth and global citizenship.